Using Occupational Therapy Models in Practice : A Fieldguide. - Turpin, Merrill (Elsevier, 2024)
Occupational therapy (OT) models provide a structured way of assessing unique contexts, such as relationships, location and cultural considerations, and how these will affect the approach to care. Written by leading experts in this field, Using Occupational Therapy Models in Practice provides a comprehensive overview of OT models and how to use them. This book goes beyond the OT curriculum to provide additional conceptual frameworks for a full range of eleven OT models. An illustrated overview of the purpose and structure of each model is provided, along with concise examples, memory aids and online case studies. Readers will come away with a detailed understanding of how to use each model in real life, making this a valuable field guide for all OT practitioners wishing to take a fully holistic approach. Fully revised to reflect the latest literature and model updates Unique in its comprehensive coverage, with an in-depth overview of eleven different models Written by internationally renowned OT practitioners and scholars Each model placed within its cultural and historical context Concise examples demonstrate how models can relate to real life situations Memory aides to guide clinical reasoning for each model Illustrations and imagery to support understanding Easy to understand and follow - suitable for OT students and practitioners Case studies for each chapter in a supporting online eBook